High Achievers, Schadenfreude and Gluckschmerz in New Zealanders and Chinese - Phillips, James G; Landhuis, C Erik; Wood, Jay K; Wang, Ying (Wiley, 2022)
The willingness to support (or denigrate) high-profile individuals online was examined across cultures using the Tall Poppy Scale. A sample of 106 Chinese and 164 New Zealand Europeans answered an online questionnaire addressing their preference for high achievers to be rewarded or fail. Participants were asked whether they would vote to support reality TV contestants, and offered further information (about success or failure) on a debrief page. The Favour Reward scale predicted willingness to vote and support others. The Favour Fall subscale tended to predict time spent viewing achievement-related information on a debrief page. The Chinese sample did not prefer reward of high achievers, instead favoring their fall, but spent less time per click on the debrief page, suggesting they disliked recognizing individual achievement.
Keywords: envy; Gluckschmerz; Guanxi; Schadenfreude; tall poppies; Gluckschmerz; Guanxi; Schadenfreude; envy; tall poppies; 52 Psychology; 5201 Applied and Developmental Psychology; 1701 Psychology; 1702 Cognitive Sciences; 5201 Applied and developmental psychology; 5203 Clinical and health psychology; 5205 Social and personality psychology; Humans; Emotions; Social Behavior; New Zealand; Reward; China; Humans; Social Behavior; Emotions; Reward; China; New Zealand; Humans; Emotions; Social Behavior; New Zealand; Reward; China